2005
DOI: 10.1111/j.1442-9071.2005.00941.x
|View full text |Cite
|
Sign up to set email alerts
|

Computerized corneal topography in a paediatric population with Down syndrome

Abstract: This study demonstrates that CVK is a useful tool in the ocular assessment of patients with Down syndrome. The findings suggest that this patient population have abnormalities of corneal shape even in the absence of clinical evidence of keratoconus. A greater than expected incidence of abnormal topographic changes was observed in the parents of these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 20 publications
1
24
0
1
Order By: Relevance
“…They include Down syndrome, 56,57 Leber's congenital amaurosis 41,58,59 and some connective tissue and collagen disorders, such as EhlersDanlos syndrome, 60 Marfan syndrom 61,62 and osteogenesis imperfecta. 63 These associations add further support for a genetic contribution to the disease and could potentially provide information on chromosomal loci.…”
Section: Association Studiesmentioning
confidence: 99%
“…They include Down syndrome, 56,57 Leber's congenital amaurosis 41,58,59 and some connective tissue and collagen disorders, such as EhlersDanlos syndrome, 60 Marfan syndrom 61,62 and osteogenesis imperfecta. 63 These associations add further support for a genetic contribution to the disease and could potentially provide information on chromosomal loci.…”
Section: Association Studiesmentioning
confidence: 99%
“…DS is a genetic condition associated with both structural and functional abnormalities. Several studies have reported that the eyes of individuals with DS have structural differences compared to aged matched populations without DS, such as thinner and steeper corneas, 24 which may contribute to the observed higher incidence of refractive error, 5, 6 as well as higher levels of astigmatism. 3, 4, 710 Many studies have also reported a higher prevalence of KC in individuals with DS, 11, 12 but it is not known if the structural differences in their thinner, more astigmatic corneas simply mimic KC, represent an incomplete (form fruste) KC, or is a truly progressive form of the disease.…”
mentioning
confidence: 99%
“…Although some authors have attributed the high prevalence of keratoconus in patients with DS to chronic eye rubbing (4,6), others have not (22). Some researchers have concluded that there are genetic aspects of the disease.…”
Section: Discussionmentioning
confidence: 99%